PERANCANGAN APLIKASI ”SIAPPARA” UNTUK PELAPORAN SETORAN E-RETRIBUSI PASAR KABUPATEN HUMBANG HASUNDUTAN - Verawaty Situmorang; Yohanssen Pratama; Riyanthi Angrainy Sianturi; Arnaldo Marulitua Sinaga (J-ICON : Jurnal Komputer dan Informatika, 2021)
Market retribution are local retribution that payed for the use of market facilities provided by the district government to individuals or entities. The process of collecting, recording, and reporting market retribution currently in Humbang Hasundutan Regency is still not effective and efficient, so it requires information technology support to enable it to improve the quality of services that are transparent and accountable in the traditional markets of Humbang Hasundutan Regency. The applications that will be developed are mobile and web-based applications that allow the collection and recording process to be more effective and efficient as well as more transparent reporting. Through the “SIAPPARA” Application, it is hoped that the process of collecting retribution in several markets in Humbang Hasundutan Regency will be easier and more transparent.